Biological parameters, immune enzymes, and histological alterations in the livers of grass carp infected with Aeromonas hydrophila. Issue 70 (November 2017) - Wang, Shen-Tong; Meng, Xin-Zhan; Li, Li-Sen; Dang, Yun-Fei; Fang, Yuan; Shen, Yubang; Xu, Xiao-Yan; Wang, Rong-Quan; Li, Jia-Le
Abstract: Aeromonas hydrophila is the causative agent of bacterial septicemia that is frequently observed in grass carp, Ctenopharyngodon idellus . In this study, we evaluated the biological parameters and immune enzymes in the liver of grass carp following A. hydrophila infection and quantified the alterations in liver histology using a semi-quantitative system. For the biological parameters, we found that the liver somatic index (LSI) was more sensitive than Fulton's condition factor (CF) and was significantly decreased at three days post-injection (DPI). At the immune enzyme level, the level of peroxidase (POD) in the liver significantly increased at 1 and 3 DPI. The activity of alkaline phosphatase (ALP) significantly increased at 3 DPI. Similarly, acid phosphatase (ACP) activity significantly increased at 1, 3, and 5 DPI. Histologically, the results indicated that the liver index at 3, 5, and 7 DPI was significantly higher than that of control groups. The regressive alterations as the highly variable reactions patterns and its index at 5 DPI was significantly higher than that of 1, 21 DPI, and the control groups. Based on our results, we suggest that grass carp resist A. hydrophila infection via an innate immune mechanism in the liver. The findings of this study will help elucidate the underlying mechanisms of resistance to A. hydrophila infection. Highlights: We attempted a novel perspective to quantified alterations observed on histology using a semi-quantitative system. We evaluated biological parameters and immune enzymes in grass carp following A. hydrophila infection. Our finding indicated the vital role of liver in innate immunity against A. hydrophila in grass carp.